2005
DOI: 10.1021/ac0507237
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Lactone Hydrolysis in Pharmaceuticals. A Tool for Metabolite Structural Characterization

Abstract: Methods to characterize metabolic transformations in a rapid and reliable fashion are required for facilitating the development of all new pharmaceuticals. One metabolic transformation, which is the focus of this study, is lactone hydrolysis. For pharmaceuticals containing lactones, hydrolysis occurs readily due to both enzymatic and nonenzymatic processes. Hydrolysis affects both the bioavailability and the efficacy of lactone-containing drugs and pro-drugs. To facilitate the characterization of lactones and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In this study, the LC-MS/MS method could not distinguish stereoscopic isomers, senkyunolide H and I, and those phthalide dimers, either naturally occurring riligustilide and levistolide A or those formed when high concentration of extracts were stored for a long period of time and induced by heat or light. MS, MS 2 , and have investigated a group of lactones related to pharmaceuticals and their corresponding hydrolysis products, carboxylic acids and discovered that they underwent different CID fragmentation pathways [11]. They have demonstrated that, under positive ESI mode, lactones had neutral losses of CO but not H 2 O and few could loose H 2 O and CO together, while acids behaved just the opposite, loosing H 2 O, H 2 O and CO together, but not CO alone.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the LC-MS/MS method could not distinguish stereoscopic isomers, senkyunolide H and I, and those phthalide dimers, either naturally occurring riligustilide and levistolide A or those formed when high concentration of extracts were stored for a long period of time and induced by heat or light. MS, MS 2 , and have investigated a group of lactones related to pharmaceuticals and their corresponding hydrolysis products, carboxylic acids and discovered that they underwent different CID fragmentation pathways [11]. They have demonstrated that, under positive ESI mode, lactones had neutral losses of CO but not H 2 O and few could loose H 2 O and CO together, while acids behaved just the opposite, loosing H 2 O, H 2 O and CO together, but not CO alone.…”
Section: Resultsmentioning
confidence: 99%
“…But up to now the interpretation of this data has been highly manual, requiring the intervention of an expert. An increasing emphasis on computer assisted spectral interpretation (67,68) can now be seen. The software products Mass Frontier (38) and ACD (61) are bringing some of these tools to the market.…”
Section: Structure Hypotheses Generationmentioning
confidence: 99%
“…Many drug candidates, including camptothecin (CPT), its analogues, and statins, contain lactone functional groups, and their efficacy is directly affected by lactone hydrolysis [3][4][5]. CPT and its derivatives are pentacyclic alkaloids containing quinoline (rings A and B), indolizinone (rings C and D), and an α-hydroxy δ-lactone moiety (ring E; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several reports have described the hydrolysis and lactonization reactions of CPTs measured by ultraviolet spectrometry (UV-vis) and spectrofluorimetry [11][12][13], capillary zone electrophoresis [14], high-performance liquid chromatography (HPLC) with ultraviolet [15], fluorescence detection [16,17], and mass spectrometry [5]. The above methods are indeed useful for measuring the rates of hydrolysis and lactonization.…”
Section: Introductionmentioning
confidence: 99%